Configurations of actual and perceived motor competence among elementary school children in China: differences in physical activity - Chai, Hongqin; Xue, Rui; Yao, Lei; Miao, Miao; Han, Bochen (Frontiers in Public Health, 2023)
Background Actual motor competence (AMC) and perceived motor competence (PMC), as determinants of children’s active participation in physical activity (PA), were important for children’s healthy development. The correlation between the two had been confirmed. To further understand this relationship, this study investigated the current status of AMC, PMC, and PA in Chinese school-age children, used a person-centered approach to reveal the characteristics of the development of motor competence (MC) in Chinese school-age children and the differences in the level of PA among different MC profiles of children. Materials and methods A total of 532 children (age: M = 9.37, SD = 1.80 years-old) from grades 1 to 6 participated in this cross-sectional study (male, n = 284, 53.4%; female, n = 248, 46.6%). The Test of Gross Motor Development-3 (TGMD-3) was used to measure children’s AMC, the Pictorial Scale of Perceived Movement Skill Competence (PMSC) to measure children’s PMC, and the revised Chinese version of Physical Activity Questionnaire for Older Children (PAQ-C) to assess children’s PA levels. Results There were some gender differences in AMC but no significant gender differences in PMC and PA in children. AMC and PA levels increased as the children aged, while PMC showed some decline. Cluster analysis identified four groups of children with different MC profiles. Two groups of children had corresponding AMC and PMC levels (the “high-high” cluster, N = 200, 38.91%; the “low-low” cluster, N = 63, 12.26%), and the other two groups were inconsistent in AMC and PMC (the “high-low” cluster, N = 100, 19.46%; the “low-high” cluster, N = 151, 29.38%). Significant differences in PA levels were found between children with different MC profiles. The “high-high” cluster children had the highest PA levels, whereas the “low-low” cluster children demonstrated the lowest PA levels. Conclusion AMC, PMC, and PA in Chinese school-age children were consistent with the pattern of child growth and development. Children with high AMC and high PMC usually had high levels of PA. Therefore, it was recommended to seize the best opportunity to intervene with children, and family, school, and community should synergize to help children improve AMC and PMC, and then actively participate in PA.